Microcapsule production by droplet microfluidics: A review from the material science approach. (November 2022) - Duran, Mikel; Serrano, Angel; Nikulin, Artem; Dauvergne, Jean-Luc; Derzsi, Ladislav; Palomo del Barrio, Elena
Graphical abstract: Highlights: Microfluidic microencapsulation is performed by various strategies based on materials, devices, and shell curing methods. Phase flow rates affect the capsule size and shell thickness in core-shell structures. Each type of shell presents its specific synthesis procedure for achieving the final stable carrier network. Biomedicine, food and cosmetic industry, self-healing, and thermal energy storage are among the main applications. Microcapsules mass production is the biggest challenge to the widespread implementation of this technology in the industry. Abstract: In the last two decades, microfluidics has emerged as a powerful tool of high precision and versatility, mainly applied to biomedicine. As a result of its strengths, the literature concerning its fundamental principles is comprehensive. Since this field continues to evolve, new areas, such as the production of solid microcapsules, need to be covered and updated. To date, some specific reviews cover microencapsulation by microfluidic focusing on the area of biology and medicine: production of microgels, controlled drug release, bacteria and cell encapsulation, and tissue engineering. Nonetheless, this technique is expanding to other research areas like material science, which can bring these materials to other applications such as food and cosmetics, self-healing materials, and energy storage industry. This work aims to cover these aspects by presenting the latest research trends in microfluidic microcapsule production. The review traces the field's evolution, showing the weaknesses and challenges faced by scientists to fully exploit the advantages of this technique. To this end, the work focuses on different facets of material science: core and shell materials; parameters affecting the capsule structure; shell curing processes; material performance; and mass production challenges. The review initially addresses the fundamentals required to understand the microcapsule formation process.